One‐Pot RT ‐ LAMP CRISPR /Cas12b Platform for Rapid Detection of Tilapia Lake Virus - Dorothea V. Megarani; Lilia Yang; Hannah J. Siler; Eva M. Quijano Cardé; Christopher J. Martyniuk; Paul M. Hick; Joy A. Becker; Esteban Soto; Win Surachetpong; Roy P. E. Yanong; Kuttichantran Subramaniam (Journal of Fish Diseases, 2026)
Tilapia Lake Virus (TiLV) is a significant threat to global tilapia aquaculture, highlighting the need for rapid and accurate diagnostic methods to manage outbreaks and minimise economic losses. This study presents the development and partial validation of a one‐pot assay integrating RT‐LAMP with the CRISPR/Cas12b system for sensitive and specific TiLV detection. This assay amplifies viral RNA using RT‐LAMP, while CRISPR/Cas12b enables a real‐time detectable signal. Targeting a conserved region in TiLV segment four, the assay achieves results within 75 min at 62°C, with easy visualisation using a portable fluorescence viewer. It demonstrated high sensitivity, with a 95% limit of detection of 79.6 copies (95% CI: 48–132 copies), and high specificity, with no cross‐reaction to other fish RNA or DNA viruses. Based on a validation panel of 261 samples from 9 source populations, the assay exhibited 92% diagnostic sensitivity (95% CI: 87%–96%) and 100% diagnostic specificity (95% CI: 97%–100%). When assessed as a non‐lethal sample, gills provided a reliable and less invasive alternative despite lower viral loads compared to internal organs. Therefore, this partially validated one‐pot assay is potentially practical for enhancing TiLV detection and disease management in aquaculture systems, especially in field settings and resource‐limited laboratories.